ChemInform Abstract: Lewis Acid‐Promoted Heterogeneous Platinum Catalysts for Hydrogenation of Amides to Amines. Issue 32 (22nd July 2016) - Shimizu, Ken‐ichi; Onodera, Wataru; Touchy, Abeda S.; Siddiki, S. M. A. H.; Toyao, Takashi; Kon, Kenichi
Abstract: Among a series of heterogeneous catalysts screened, Pt‐Nb2 O5 shows the highest catalytic activity in the selective hydrogenation of various tertiary amides (I) and caprolactams (III) to the corresponding amines (II) and (IV), resp.